UNITED NATIONS IN THE FIGHT AGAINST TERRORISM (with special emphasis on the position of the Arab authors) - Abo Saeid, Tarek (Scientific Journal of Bielsko-Biala School of Finance and Law, 2014)
The author analyzes the mechanisms of terrorist activity and its causes. He also brings closer the methods of counteracting and fighting terrorism used by the international community within the UN over time and in the light of international events. The paper lists the tools and legal instruments aimed at protecting human rights in the context of terrorism and in prevention of terrorist attacks.